2008
DOI: 10.1590/s1807-76922008000400003
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of discretionary firm donations in Brazil

Abstract: BSTRACTDiscretionary firm donation is usually related to the stakeholder theory and corporate social performance. Although theoretical explanations for this social behavior are pervasive in related literature, empirical modeling remains underdeveloped. We developed an explanatory structural model of discretionary firm donation using firm and industry level indicators. Unlike previous research, we estimated the explanatory power of the construct we called stakeholder orientation. Our tentative model was tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
3
0
6
Order By: Relevance
“…Literature has found that profitability (Adams and Hardwick, 1998;Crampton and Patten, 2008;Seifert et al, 2003) and leverage (Roberts, 1992;Adams and Hardwick, 1998) are associated with corporate philanthropic giving. Profitability (ROA), as in Bandeira- de-Mello et al (2008), is measured as the "Return on Assets" in 2007. Leverage (LEVE) is measured as the ratio of total debt to the total value of assets in 2007.…”
Section: Measurement Of Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature has found that profitability (Adams and Hardwick, 1998;Crampton and Patten, 2008;Seifert et al, 2003) and leverage (Roberts, 1992;Adams and Hardwick, 1998) are associated with corporate philanthropic giving. Profitability (ROA), as in Bandeira- de-Mello et al (2008), is measured as the "Return on Assets" in 2007. Leverage (LEVE) is measured as the ratio of total debt to the total value of assets in 2007.…”
Section: Measurement Of Variablesmentioning
confidence: 99%
“…Therefore, to support (or defy) institutional viewpoint of corporate philanthropy, more evidences are needed. Besides, in spite of theoretical pervasiveness, empirical research on corporate donation activities needs developing (Bandeira- de-Mello et al, 2008), especially the empirical research in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Entre los autores sobresale también el rol protagónico que desempeñan los investigadores Rodrigo Bandeira de Mello, coautor de cuatro artículos y Rosilene Marcon, de tres de ellos. En estos artículos resalta el estudio del caso brasileño (Bandeira de Mello et al, 2008;Bandeira de Mello y Marcon, 2005;Costa et al, 2013;Vieira Bazuchi et al, 2013). En un solo artículo se consideran otros contextos latinoamericanos (Rufín, Parada y Serra, 2008).…”
Section: Temáticas De Investigación Sobre Contextos Latinoamericanosunclassified
“…En la relación entre contexto y acción política se investigó sobre indicadores a nivel de la firma y del sector, para explicar las donaciones de empresas brasileñas transadas en bolsa. Cabe resaltar que entre las donaciones se incluyen tanto los aportes a proyectos sociales como a las campañas políticas (Bandeira de Mello et al, 2008).…”
Section: Temáticas De Investigación Sobre Contextos Latinoamericanosunclassified
“…Segundo, o ponto de vista considerado nos estudos internacionais é preferencialmente o das firmas de países desenvolvidos ou multinacionais que se instalam em países emergentes. Explicações sobre como firmas locais lidam com o governo local e como essa relação pode beneficiá-las estão em desenvolvimento (Bandeira-de-Mello, Marcon, & Alberton, 2008;Brey, Camilo, Marcon, & Bandeira-de-Mello, 2013;Costa, Bandeira-de-Mello, & Marcon, 2013;Fernandes, Bandeira-de-Mello, & Zanni, 2012;Lazzarini, 2011;Samuels, 2001). Apesar do avanço democrático e do fortalecimento das instituições de mercado, como os intermediários financeiros, os mercados de capitais e os marcos regulatórios, o ambiente político das firmas no Brasil continua exercendo um papel importante nas decisões estratégicas (Bandeira-de-Mello & Marcon, 2005).…”
Section: Estratégias De Incentivo Financeirounclassified